A Low-Cost, Accurate, and High-Precision Fluid Dispensing System for Microscale Application. (April 2017) - Das, Champak; Wang, Guochun; Nguyen, Chien
We present here the development of a low-cost, accurate, and precise fluid dispensing system. It can be used with peristaltic or any other pump to improve the flow characteristics. The dispensing system has a range of 1 to 100 µL with accuracy of ~99.5% and standard deviation at ~150 nL over the entire range. The system developed does not depend on the accuracy or precision of the driving pump; therefore, any positive displacement pump can be used to get similar accuracy and precision, which gives an opportunity to reduce the cost of the system. The dispensing system does not require periodic calibration and can also be miniaturized for microfluidic application. Although primarily designed for aqueous liquid, it can be extended for different nonconductive liquids as well with modifications. The unit is further used for near real-time measurement of lactate from microdialysate. The individual components can easily be made disposable or sterilized for use in biomedical applications.